PEMANFAATAN APLIKASI PHYSIC CLASSROOM UNTUK MENINGKATKAN PEMAHAMAN TENTANG PEMANTULAN CAHAYA PADA CERMIN DATAR - Fadia Risma Afrisia Salsabila; Muji Hikmatul Janah; Fina Umi Fadlila Armayasari; Riva Ismawati (ScienceEdu, 2022)
Natural Sciences (IPA) is the study of natural phenomena and everything in nature which includes three branches, namely physics, chemistry, and biology. Learning physics is very closely related to concepts, theories, and mathematical calculation formulas, which are interrelated with one another. However, in the learning process, not all students can fully absorb and understand information. So that it raises misconceptions or differences in knowledge between students and the concepts of experts. This study aims to compare students' understanding of light reflection material with manual experiments and using the physics classroom application. The rules used in this investigation are quantitative with ekperimental techhniques. The study was conducted with a learning trial on students 8th grade of junior high school 1 Temanggung. The results of the data are done by counting the number of students who understand the theory by filling out questionnaires. The results showed that many students were more aware of the reflection material using the physics classroom application.